Evolvable data model decomposition for hydropower dispatching networks via collaborative intrusion detection - Duan, Ruiqin; Jiang, Yan; Chen, Ruchang; Zhu, Xinchun; Liu, Shuangquan; Wu, Yang (Frontiers in Physics, 2025)
To maximize the operational value of hydropower stations and achieve expected economic benefits, efficient dispatching and command operations are essential. With the growing dimensionality of indicator data in hydraulic engineering, traditional methods face challenges in handling complex multi-dimensional spatial data modeling. In particular, traditional Kalman filtering methods often suffer from the “curse of dimensionality” during model solving, resulting in long computation times and model instability. This paper proposes an approach based on an evolvable data model decomposition for hydropower dispatching networks, leveraging collaborative intrusion detection techniques. The improved Kalman filtering algorithm structure is designed to tackle multi-stage dynamic decision-making processes involving multi-regular state function parameters. By decomposing single-stage primary problems into multiple elementary subproblems, the operational principles of multi-dimensional spatial analysis are modified. Through function simplification and rational point-wise problem allocation, priority conditions for global optimization of decision processes are established, thus promoting the optimization of multi-dimensional space folding and movement velocities. In the construction of stochastic multi-dimensional spaces, optimized stochastic indicator models and parametric simulation designs are employed. The initial step is to define hydropower dispatching strategies, which are compared with explicit model stochastic optimization while ensuring load output requirements and cost-benefit constraints. Guided by the aggregation concept of decomposable indicators, an implicit stochastic optimal dispatching boundary is established, forming a data transfer function model for hydropower scheduling. The collaborative intrusion detection mechanism plays a crucial role in safeguarding the security and reliability of the data model decomposition process, ensuring the robustness of the overall system. Finally, the operation and analysis of the simulation system validate the guiding role of the dispatching functions in hydropower systems. The results demonstrate that the proposed hydropower scheduling solution, with its evolvable data model decomposition and collaborative intrusion detection, exhibits superior operability and practical utility for operational dispatching command tasks in hydraulic engineering projects. This methodology provides an effective technical pathway for addressing complex scheduling challenges in modern hydropower systems, offering a new perspective on enhancing the efficiency and security of hydropower dispatching networks.